SPECTRUM EFFICIENCY IN CELLULAR MOBILE RADIO SYSTEMS WITH MULTIPLE CORRELATED SIGNALS - SAFAK, A (I E E E, 1994)
[Abstract Not Available]
7th Mediterranean Electrotechnical Conference (MeleCON 94) -- APR 12-14, 1994 -- ANTALYA, TURKEY